A combined recombinase polymerase amplification CRISPR/Cas12a assay for detection of Fusarium oxysporum f. sp. cubense tropical race 4 - Megan Ceris Matthews; Jos van der Linden; Isabelle Robène; Samuel Rozsasi; Beatrix Coetzee; Manuela Campa; Johan Burger; Uzoma Nobel Akwuruoha; Ndubuisi Johnkennedy Madufor; Willem Perold; Umezuruike Linus Opara; Altus Viljoen; et al. (Scientific Reports)
Abstract The soilborne pathogen Fusarium oxysporum f. sp. cubense tropical race 4 (Foc TR4) is currently devastating banana production worldwide. Once introduced, it is not possible to eradicate the pathogen from soils where it can survive for decades. The only management option available then is to replace Foc TR4-susceptible with -resistant varieties. Timely detection of the pathogen, however, is an important strategy to prevent the introduction of Foc TR4 into new areas and prevent its spread from infested sites. In this study, a single-tube detection technique was developed by combining recombinase polymerase amplification (RPA) and clustered regularly interspaced short palindromic repeats (CRISPR)/Cas12a technology (RPA-Cas12a) for detection of Foc TR4. The RPA-Cas12a assay was conducted isothermally, had a sensitivity of up to 10 fg target DNA and did not cross react with any of the 76 non-target isolates included in the specificity testing. The RPA-Cas12a assay detected Foc TR4 from naturally infected banana samples collected in the field and visualization was possible with the naked eye under LED blue light transillumination. The method can be integrated with inexpensive fluorescent or electronic detection devices to accelerate Foc TR4 in-field detection and, thereby, fast-track disease containment strategies.